A eficiência ambiental nas edificações: fundamentos e estratégias para a elaboração do projeto arquitetônico a partir do uso racional de energia elétrica e água - Andre Luiz Prado de Oliveira (2005)
This work, aims to discuss questions related to the use of electric energy and water on buildings nowadays, considering the increasing scarcity of natural resources. Possibilities of naturally introducing these questions during the architectural project elaboration process arediscussed along the text, contributing, therefore, to establish a more rational use of these resources. The core of the research is the creation of a methodological guide that creates a basis of scientific and technical fundaments as well as project strategies that can be considered in thearchitectural elaboration process. It is also part of this research, a brief historical revision about the introduction of environmental concernments in the Brazilian architecture, during the period that modernism reached the country, and a revision of the state of art of engineering technologiesrelated to the building environmental efficiency. A case study completes this research: an environmental efficiency building project course, give in the EAUFMG graduation course, which worked as a basis for the methodological guide.